Derivation of paleolongitude from the geometric parametrization of apparent polar wander path: Implication for absolute plate motion reconstruction - Wu, Lei; Kravchinsky, V. (American Geophysical Union, 2014)
Obtaining ancient longitude position of continents in the past has always been a challenge for plate tectonic reconstructions. Paleomagnetism has been commonly used to reconstruct paleolatitudes and relative rotations but not paleolongitudes. In this work, we present a synthesized method to derive paleolongitude by geometrically parametrizing apparent polar wander path (APWP). Great and small circle modeling are implemented concurrently to the identified APWP tracks to calculate the paleomagnetic Euler parameters (stage rotation pole and rotation angle). From the Euler parameters of the optimal fitting option, the absolute motion history can be restored for the reference geometries. Using our method as well as the results from relative plate motion studies, we reevaluate the dispersion history of East Gondwana since 140 Ma. To further test the validity of our method, we compare the predictions from four other absolute motion models mainly in paleolatitude movement, longitudinal variation, and great circle distance, which suggest the most similarity with the global hybrid reference frame. Key Points Great and small circle APWP parametrization with paleocolatitude correction Paleolongitude can be derived from apparent polar wander path Reconstruction of East Gondwana since 140 Ma is reevaluated ©2014. American Geophysical Union. All Rights Reserved.